2001
DOI: 10.1161/01.cir.103.21.2566
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mortality by Exercise Echocardiography

Abstract: Background-In studies generally involving short follow-up, exercise echocardiography has been shown to predict composite end points. We sought to study the prediction of mortality with this test and to devise a strategy for combination with standard exercise testing. Methods and Results-Clinical, exercise testing, and echocardiographic data were collected in 5375 patients (aged 54Ϯ14 years, 3880 men) undergoing exercise echocardiography. The Duke treadmill score was derived from the results of treadmill exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(47 citation statements)
references
References 30 publications
3
36
1
7
Order By: Relevance
“…22 Multivariate analysis of our data showed ischemia or the finding of an abnormal stress echocardiogram to be an independent predictor of mortality in hypertensive patients, and all of these data are consistent with previous reports in unselected patients with both exercise 5 and dobutamine echocardiography. 6…”
Section: Marwick Et Al Prediction Of Cardiac Death In Hypertensionsupporting
confidence: 91%
See 2 more Smart Citations
“…22 Multivariate analysis of our data showed ischemia or the finding of an abnormal stress echocardiogram to be an independent predictor of mortality in hypertensive patients, and all of these data are consistent with previous reports in unselected patients with both exercise 5 and dobutamine echocardiography. 6…”
Section: Marwick Et Al Prediction Of Cardiac Death In Hypertensionsupporting
confidence: 91%
“…19,20 Recent studies with exercise and dobutamine echocardiography have shown the yearly event rate with a negative test to be of the order of 1% per year. 5,6 The results of this study of hypertensive patients are consistent with the data obtained in nonhypertensive patients. Previous studies have shown that patients who have events despite a negative test tend to be older, have a history of heart failure, exercise to low workload, or have anginal symptoms or left ventricular hypertrophy.…”
Section: Assessment Of Prognosissupporting
confidence: 89%
See 1 more Smart Citation
“…15 Although poor exercise capacity is recognized as an adverse prognostic element, studies which have examined the sensitivity of ETT for the diagnosis of CAD have used the criterion of 85% MPHR as an "adequate" test even if the patient has not exercised beyond 5 METS. 3,4,9 These patients, in general, are deconditioned and achieve their target heart rate in a short period of time. Thus, although their estimated workload (by rate-pressure product) may be adequate, their extent and exposure time to an ischemic supply-demand condition is limited, potentially resulting in a lower sensitivity for an ischemic electrical response in this cohort.…”
Section: Prognostic Value Of the Exercise Treadmill Testingmentioning
confidence: 99%
“…5 -8 Previous studies comparing ESE to ETT have included patients achieving a low workload despite adequate heart rate response, potentially biasing the results against ETT. 3,4,9 Therefore, we hypothesized that given stringent standards of exercise duration and ECG interpretability, the ETT would have a high diagnostic sensitivity for the presence of CAD. Support of this hypothesis would potentially limit the necessity and cost of adjunct echocardiographic imaging in many patients.…”
Section: Introductionmentioning
confidence: 99%